Strain-Modulated and Nanorod-Waveguided Fluorescence in Single Zinc Oxide Nanorod-Based Immunodetection - Marion Ryan C. Sytu; Andrew Stoner; Jong-In Hahm (Biosensors, 2024)
Mechanical strain has been shown to be a versatile and tunable means to control various properties of nanomaterials. In this work, we investigate how strain applied to individual ZnO nanorods (NRs) can affect the fluorescence signals originated from external sources of bioanalytes, which are subsequently coupled and guided onto the NRs. Specifically, we determine how factors such as the NR length and protein concentration can influence the strain-induced changes in the waveguided fluorescence intensity along the NRs. We employ a protein of tumor necrosis factor-α (TNF-α) and a fluorophore-labeled antibody in a model immunoassay reaction, after which Alexa488-TNF-α immunocomplex is formed on ZnO NRs. We elucidate the relationships between the types as well as amounts of strain on the NRs and the fluorescence intensity originated from the Alexa488-TNF-α immunocomplexes. We show that tensile (compressive) strain applied to the NR leads to an increase (decrease) in the waveguided fluorescence signals. By assessing important optical phenomena such as fluorescence intensification on nanorod ends (FINE) and degree of FINE (DoF), we confirm their linear dependence with both the types and amounts of strain. Furthermore, the strain-induced changes in both FINE and DoF are found to be independent of protein concentration. We determine that NR length plays a critical role in obtaining high strain-dependence of the measured fluorescence signals. Particularly, we ascertain that longer NRs yield larger changes in both FINE and DoF in response to the applied strain, relative to shorter ones. In addition, longer NRs permit higher linear correlation between the protein concentration and the waveguided fluorescence intensity. These outcomes provide valuable insight into exploiting strain to enhance the detection of optical signals from bioanalytes, thus enabling their quantifications even at ultra-trace levels. Coupled with the use of individual ZnO NRs demonstrated in our measurements, this work may contribute to the development of a miniaturized, highly sensitive biosensor whose signal transduction is best optimized by the application of strain.